Instructional design models for immersive virtual reality: a systematic literature review - Castelhano, Maria (2023)
The emergence of accessible virtual reality headsets in the past decade multiplied educational uses of immersive virtual reality. Higher education, in particular, has seen many such reports emerge. However, there are scarce frameworks for higher education professionals to plan and deploy immersive virtual reality within their pedagogical practice. To attain a perspective on this field, we conducted a systematic literature review using SCOPUS search, focusing on Instructional Design Models for Immersive Virtual Reality in online Higher Education. This review aimed to provide a comprehensive overview of these models, their respective phases, and distinctive characteristics. The review identified two categories of Instructional Design Models for Immersive Virtual Reality in Higher Education: 1) Models specific to such contexts, with aspects such as managing immersion time or providing prior contact with the immersive environment; 2) Models developed for other contexts and adapted to immersive virtual reality, addressing aspects such as the importance of creating objectives, assessment elements, or defining resource purpose. We conclude that current instructional models used for immersive virtual reality in higher education lack the combination of the overall pedagogical concerns with the specific ones for immersive virtual reality. Thus, we recommend further research to develop instruction models that combine both aspects of learning design concerns.